The Relationship between Service Quality and Hajj’s Applicant Satisfaction Study: The Administration Process, Banyumas Regency - Robbany, Ricky Bayu (Jurnal Ilmiah Administrasi Publik, 2018)
Hajj is an annual Islamic pilgrimage to Mecca, the holiest city for Moslems. The purpose of this research is to examine the relationship between service quality and Hajj applicant’s satisfaction. The research shows that service quality have a positive influence with the satisfaction. Applicant believes that among the five factors in service quality, namely tangible, reliability, empathy, and assurance (the highest) have good results while responsiveness requires to be improved. Consumers hope that the government will improve the service on Hajj application and its introduce a new, as least method to increase satisfaction.